4 Opiate use is associated with reduced antiplatelet drug effect and raised troponin in PPCI. (27th November 2017) - Farag, Mohamed; Spinthakis, Nikolaos; Srinivasan, Manivannan; Sullivan, Keith; Wellsted, David; Gorog, Diana A
Abstract : Background: Emergency management of ST-elevation MI (STEMI) involves administration of dual antiplatelet therapy (DAPT) and primary percutaneous intervention (PPCI). Pain is conventionally treated with IV morphine that may reduce absorption of DAPT. We aimed to assess the effect of morphine on thrombotic status in STEMI patients. Methods: Thrombotic status was assessed in 300 patients with STEMI, all of whom had DAPT and some received morphine analgesia as clinically indicated. Blood was taken immediately before PPCI and on day 2 on DAPT. Thrombotic status was assessed using the point-of-care Global Thrombosis Test that measures time to form an occlusive thrombus (occlusion time, OT), and time to restore flow by endogenous thrombolysis (lysis time, LT). Results: Morphine-treated patients (73%) exhibited enhanced platelet reactivity, with shorter OT (347±150 s vs 547±182 s; p<0.001) and reduced thrombolytic potential with longer LT (1402s [1159–1809] vs 1185s [1029–1541]; p=0.001) compared to no-morphine patients. By day 2, no difference was apparent in OT whilst LT remained slightly longer in the morphine group. Patients receiving morphine had reduced TIMI flow in the infarct-related artery pre-PPCI, and higher peak troponin T level post-PPCI (1906 [1002–4398] vs 1268 [249–2920]; p=0.016) than those without. Conclusions: Compared to STEMI patients without morphine, patients receiving morphine had higher platelet reactivity on arrival despite DAPT, and higher subsequent peak troponin. Opiates likely delay absorption of DAPT, which may impact on myocardial salvage.